THE RELATIONSHIP OF PHYSICAL SELF-CONCEPT AND PARENT SUPPORT WITH THE CONFIDENCE OF JUNIOR HIGH SCHOOL STUDENTS - Mutia Lukman, Suci; Yusuf, A Muri; Syukur, Yarmis; Nurfarhanah, Nurfarhanah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This research is motivated by a phenomenon that occurs in the UNP Laboratory Development Junior High School, namely the low self-confidence of students. Physical self-concept and parental support are factors that affect students' self-confidence. This study aims to analyze (1) physical self-concept, (2) parental support, (3) self-confidence, (4) the relationship between physical self-concept and student self-confidence, (5) the relationship between parental support and student self-confidence and (6) the relationship between physical self-concept and parental support with student self-confidence. The research method used is quantitative. This type of research is descriptive correlational. The sample of this research was 163 students. Sampling using the Slovin formula and sampling using proportional random sampling technique. The research instrument is a questionnaire with Likert Scale measurements, the data were analyzed by correlational descriptive statistics with the help of SPSS version 20.00. The results showed that (1) the students' physical self-concepts were in the high category, (2) the student's parental support was in the high category, (3) the students' self-confidence was in the high category, (4) there was a positive relationship and significant relationship between physical self-concept and students' self-confidence, (5) there is a positive and significant relationship between parental support and student self-confidence, and (6) there is a positive and significant relationship between physical self-concept and parental support and student self-confidence. So, it can be concluded that there is a positive and significant relationship between physical self-concept and parental support with student self-confidence